Social media and public participation of Tablighi Jamaat’s women - Isnaini, Syarifah (Faculty of Communications Science, Dr. Soetomo University, 2022)
Since the study of women in the Tablighi Jamaat (JT) has been actively promoted by various layers and circles in the academic environment, a thesis has also been gradually obtained, strengthening the position of most JT women who live in private and domestic spaces. This study was born from an investigation into the teachings of JT, which are quite strict in regulating the ethics of women's interactions. Also, JT women, like followers of the reformist Islamic movement, do not have a history of good relations with Western products such as social media. The conditions obtained by various previous studies became unstoppable when discussing the women of JT in Temboro Village, Magetan. In this village, which is the central headquarters of JT in East Java, women are often found participating in public spaces and familiar with social media, which is a Western product. By using the post-Islamism theory and ethnographic method, the writer hypothesises that JT Temboro women go through a separate negotiation process related to JT's teachings with the decision to participate in public spaces, one of which is influenced by their intensity with social media.